IDIOMS IN ARABIC AND ENGLISH: DIVERSITIES AND SYMMETRIES - Hasanain Hasan Shaheed; Najlaa Hayyawi Abbar; Wisam Sarmad Hussein (Scholar Express Journal, 2022)
The current study deals with one of the most important topic within linguistics in general and within semantics in particular which is called idioms. This notion denotes a set of two or more orthographic words which sense cannot be deduced from the sense of the component parts. The problem of the study is that some learners face difficulties within interpretation of the idiom phenomenon. The study also aims at re-visiting the concept of "idiom" and its details in both English and Arabic. It is hypothesized that "idioms" usually more employed in Arabic than in English. To perform its aims and confirm its hypothesis, the study adopts the following steps: (i) Defining the notion of "idiom" in both English and Arabic. (ii) Stating the structure of "idiom" in both English and Arabic. (iii) Coming out with a number of conclusions. The result is that Arabic is used "idiom" more than English
Keywords: Idiom; Words; Lexical; Identical